Increased Neutrophil Secretion Induced by NLRP3 Mutation Links the Inflammasome to Azurophilic Granule Exocytosis - Johnson, Jennifer L.; Ramadass, Mahalakshmi; Haimovich, Ariela; McGeough, Matthew D.; Zhang, Jinzhong; Hoffman, Hal M.; Catz, Sergio D. (Frontiers in Cellular and Infection Microbiology, 2017)
Heterozygous mutations in the NLRP3 gene in patients with cryopyrin associated periodic syndrome (CAPS) lead to hyper-responsive inflammasome function. CAPS is a systemic auto-inflammatory syndrome characterized by the activation of the innate immune system induced by elevated pro-inflammatory cytokines, but the involvement of selective innate immune cells in this process is not fully understood. Neutrophil secretion and the toxic components of their granules are mediators of inflammation associated with several human diseases and inflammatory conditions. Here, using the Nlrp3A350V inducible mouse model (MWS CreT) that recapitulates human patients with the A352V mutation in NLRP3 observed in the Muckle-Wells sub-phenotype of CAPS, we studied the relationship between hyper-activation of the inflammasome and neutrophil exocytosis. Using a flow cytometry approach, we show that Nlrp3A350V (MWS) neutrophils express normal basal levels of CD11b at the plasma membrane and that the upregulation of CD11b from secretory vesicles in response to several plasma membrane or endocytic agonist including the bacterial-derived mimetic peptide formyl-Leu-Met-Phe (fMLF) and the unmethylated oligonucleotide CpG is normal in MWS neutrophils. Significant but modest CD11b upregulation in MWS neutrophils was only observed in response to GM-CSF and CpG. The same pattern was observed for the secretion of matrix metalloproteinase-9 (MMP-9) from gelatinase granules in that MMP-9 secretion in MWS neutrophils was not different from that observed in wild-type neutrophils except when stimulated with GM-CSF and CpG. In contrast, azurophilic granule secretion, whose cargoes constitute the most toxic secretory and pro-inflammatory factors of the neutrophil, was markedly dysregulated in MWS neutrophils under both basal and stimulated conditions. This could not be attributed to paracrine effects of secretory cytokines because IL-1 secretion by neutrophils was undetectable under these experimental conditions. The increased azurophilic granule exocytosis in MWS neutrophils was attenuated by treatment with the neutrophil exocytosis inhibitor Nexinhib20. In agreement with a possible neutrophil contribution to systemic inflammation in CAPS, the levels of neutrophil secretory proteins were significantly elevated in the plasma from Nlrp3A350V mice. Altogether, our data indicates an azurophilic granule-selective dysregulation of neutrophil exocytosis in CAPS.